Carrier lifetime and breakdown phenomena in SiC power device material. (30th July 2018) - Kimoto, T; Niwa, H; Okuda, T; Saito, E; Zhao, Y; Asada, S; Suda, J
Abstract: Recent progress and current understanding of carrier lifetimes and avalanche phenomena in silicon carbide (SiC) are reviewed. The acceptor level of carbon vacancy ( V C ), called the Z 1/2 center, has been identified to be the primary carrier lifetime killer in SiC. The V C defects can be eliminated by the introduction of excess carbon atoms followed by carbon diffusion in the bulk region. The true bulk lifetime after V C elimination was estimated to be approximately 110 µ s. The doping dependence of carrier lifetimes in n- and p-type SiC is also presented. The impact ionization coefficients of electrons and holes were extracted in the temperature range of 298 to 423 K. The intrinsic critical electric field strength of SiC⟨0 0 0 1⟩ was determined to be 2.0, 2.5, and 3.3 MV cm −1 for doping densities of 1 × 10 15, 1 × 10 16, and 1 × 10 17 cm −3, respectively, at room temperature; it slightly increased at elevated temperature. The obtained set of impact ionization coefficients has enabled us to accurately predict the breakdown voltage of SiC devices, including its temperature dependence. Due to the unusually low impact ionization coefficient of electrons, the breakdown voltage of a SiC p + n junction is about 6%–9% higher than that of an n + p junction with a given doping density.